2009
DOI: 10.1063/1.3186030
|View full text |Cite
|
Sign up to set email alerts
|

Ion engineering of embedded nanostructures: From spherical to facetted nanoparticles

Abstract: We show that the high-energy ion irradiation of embedded metallic spherical nanoparticles ͑NPs͒ is not limited to their transformation into prolate nanorods or nanowires. Depending on their pristine size, the three following morphologies can be obtained: ͑i͒ nanorods, ͑ii͒ facettedlike, and ͑iii͒ almost spherical nanostructures. Planar silica films containing nearly monodisperse gold NPs ͑8-100 nm͒ were irradiated with swift heavy ions ͑5 GeV Pb͒ at room temperature for fluences up to 5 ϫ 10 13 cm −2 . The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…The effects of swift heavy-ion irradiation on metallic NPs embedded in SiO 2 have been studied by different groups [60,61,64,65,67] who observed that, during irradiation, the silica matrix dilates perpendicular to the beam direction, while the metallic NP deforms and elongates along the beam direction. Moreover, the deformation and elongation of the metallic NP depends on its initial size and shape, its chemical composition, the irradiation fluence, and the position where the NP is placed in the matrix with respect to the substrate [67].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of swift heavy-ion irradiation on metallic NPs embedded in SiO 2 have been studied by different groups [60,61,64,65,67] who observed that, during irradiation, the silica matrix dilates perpendicular to the beam direction, while the metallic NP deforms and elongates along the beam direction. Moreover, the deformation and elongation of the metallic NP depends on its initial size and shape, its chemical composition, the irradiation fluence, and the position where the NP is placed in the matrix with respect to the substrate [67].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Small fluctuations in the elongation rate are nonetheless observed [see Figs. 1(b)-1(d)], as prolate nanoparticles originating from smaller or bigger nanospheres, respectively, evolve further away or less far at the same fluence values (see previous work [65,67,71] for a quantitative study of the shaping of gold nanoparticles by a swift heavyion beam).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, recently other groups have experimentally shown the elongation of Au NPs as large as 45 nm in diameter. 21,25 Awazu et al did not propose any scenarios from the melting to the elongation, except briefly suggesting a possible role of the in-plane stress of the SiO 2 matrix. This model was also suggested by Oliver et al 11 Ridgway et al also pointed out 19 that Co NPs larger than 50 nm in diameter showed elongation under 196-MeV Au irradiation, while thermal spike calculations predicted that only Co NPs smaller than 20 nm in diameter should elongate.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] The response of the material to SHI mainly depends upon the type of the material, its fabrication parameters, the stoichiometry and the characteristics of the ions. These ions can create disorder in the form of point defects, cluster defects, amorphous track, or a perturbed atomic distribution along its path as they pass through the material.…”
mentioning
confidence: 99%